La influencia de los grupos de interés en la política ambiental: Breve discusión desde la teoría de juegos (2008)
This is a literature review on interest groups, particularly about the interaction between interest groups and an environmental conservation agency. At the same time, the possibilities of testing empirically the equilibriums predicted by these models are explored. This provides a way of determining if public policy conforms to public interest or interest groups theories.